Endangered monk seals - Kalman, Bobbie. frey50 (New York, NY : Crabtree Pub., 2004)
Describes monk seals, where they live, what they eat, dangers they face, and efforts to help them.
Endangered animals -- Two monk seal species left -- Monk seals are mammals -- What are pinnipeds? -- Built for swimming -- Monk seal habitats -- Finding food -- A monk seal's life cycle -- Mothers and pups -- Fewer babies -- Habitat destruction -- Other dangers -- Helping monk seals -- How you can help.
Includes index.
Keywords: Monk seals; Endangered species; Monk seals; Seals (Animals); Endangered species